2021
DOI: 10.3390/life11050432
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Mitochondrial Protein Import and Respiratory Complexes Assembly in Neuronal Health and Degeneration

Abstract: The fact that >99% of mitochondrial proteins are encoded by the nuclear genome and synthesised in the cytosol renders the process of mitochondrial protein import fundamental for normal organelle physiology. In addition to this, the nuclear genome comprises most of the proteins required for respiratory complex assembly and function. This means that without fully functional protein import, mitochondrial respiration will be defective, and the major cellular ATP source depleted. When mitochondrial protein impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 382 publications
(529 reference statements)
0
25
0
Order By: Relevance
“…NDUFA11 is one of the many supernumerary subunits of mammalian respiratory complex I, with homologues in Neurospora crassa (NUO21.3b) ( Hirst et al, 2003 ) and plants (B14.7, also known as OEP163 in Arabidopsis ) ( Wang et al, 2012 ). Interestingly, NDUFA11 also shares homology with the essential Tim17 family ( Žárský and Doležal, 2016 ), including Tim17 and Tim23, which are core subunits of the TIM23 complex, and Tim22 at the centre of the TIM22 complex (reviewed by Needs et al, 2021 ). The importance of NDUFA11 as a complex I subunit was established in N. crassa and human cell culture studies, which revealed that impaired NDUFA11 levels lead to the incomplete assembly of complex I ( Andrews et al, 2013 ; Nehls et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…NDUFA11 is one of the many supernumerary subunits of mammalian respiratory complex I, with homologues in Neurospora crassa (NUO21.3b) ( Hirst et al, 2003 ) and plants (B14.7, also known as OEP163 in Arabidopsis ) ( Wang et al, 2012 ). Interestingly, NDUFA11 also shares homology with the essential Tim17 family ( Žárský and Doležal, 2016 ), including Tim17 and Tim23, which are core subunits of the TIM23 complex, and Tim22 at the centre of the TIM22 complex (reviewed by Needs et al, 2021 ). The importance of NDUFA11 as a complex I subunit was established in N. crassa and human cell culture studies, which revealed that impaired NDUFA11 levels lead to the incomplete assembly of complex I ( Andrews et al, 2013 ; Nehls et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…( F ; purple ) Transmembrane helices of the OMM with a noncleavable signal anchor sequence are imported by MIM directly into the OMM, with assistance only from Tom70. Figure inspired from ( 2 , 9 , 187 ). IMM, inner mitochondrial membrane; IMS, intermembrane space; MIA, mitochondrial intermembrane space assembly; MIM, mitochondrial import machinery; OMM, outer mitochondrial membrane; SAM, sorting and assembly machinery; TIM, translocase of the inner mitochondrial membrane; TOM, translocase of the outer mitochondrial membrane.…”
Section: Mitochondrial Preprotein Importmentioning
confidence: 99%
“…Mitochondrial dysfunction, which often relates to import-associated defects ( 185 ), leads to several neurodegenerative and age-related disorders. Mitochondria play a pivotal role in the pathogenesis of Huntington's disease, Parkinson's disease, and Alzheimer’s disease ( 158 , 186 , 187 , 188 , 189 ). Nearly all diseases arising from mutagenesis or gene polymorphism have been identified for the inner membrane complexes.…”
Section: Tom Dysregulation and Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurodegeneration and primary mitochondrial diseases, triggered by a defective respiratory chain, comprise impaired respiratory complex assembly and function. However, Needs et al [10] consider that mitochondrial protein import is important for normal organelle physiology and observed an interlink with the regulation of respiratory complex assembly and function in human diseases. Moreover, in the paper by Franco et al, the human mitochondrial disorders that affect the OXPHOS activity have been suggested to be studied by using the Saccharomyces cerevisiae as a model to gain an understanding of the underlying molecular consequences of pathogenic mutations in mitochondria [11].…”
mentioning
confidence: 99%